Individual Responsibility & Command Responsibility on Serious Human Rights Violation in Indonesia - Amirudin Imam Nur; Hanafi Mursyid Wijanarko; Pryo Sularso (Universitas PGRI Madiun, 2021)
The wave of reform in Indonesia that was rolling in the context of overthrowing the New Order was full of abuse of power, corruption, collusion, nepotism (KKN) and human rights violations. Application of the concept of a direct law enforcement system against the category of international crimes, which in the past emphasized the national justice jurisdiction (indirect enforcement system). Cases of human rights violations are very interesting, because the crimes that occur have a special condition which by experts call it a special form of political crime. The research method in this study is a normative juridical research method, which means that this research is sourced from library data. The legal issue in this research is How is the individual and command responsibilities in Serious Human Rights Violations in Indonesia. The results of this research show that Indonesia is currently under the spotlight internationally in connection with the indictment of gross human rights violations, especially in the issues of East Timor, Tanjung Priok and so on. The universal principle that it is impossible to treat gross human rights violations as